PERSEPSI DAN KESIAPAN MASYARAKAT TERHADAP POTENSI NUKLIR SEBAGAI PEMBANGKIT LISTRIK - Anantha Ivan Wijaya; Ariana, Puspita; Hidayah, Rahmat Rifaldi (JPFT (Jurnal Pendidikan Fisika Tadulako Online), 2021)
Indonesia is a country that has a variety of opinions on nuclear. Many people still do not know the understanding of nuclear and its usefulness. Indonesia already has a plan regarding the construction of nuclear power plants and is already under consideration. Readiness of the Community for development has a variety of readiness Research conducted is quantitative research aimed at knowing the perception and readiness of the community related to nuclear technology as a power plant. The study was conducted in the form of questionnaires filled out through Google Form. The variables in this study contain Independent Variables (X) namely nuclear and dependent variables (Y) that are perspectives and public awareness. Based on research conducted using questionnaires that use the Likert scale. The conclusion of the questionnaire results conducted has a comparison of people who agree with disapproval in the manufacture of nuclear power plants and the existence of nuclear technology has a considerable comparison. For the readiness of the community to the impact that will be caused by the nuclear power plant, it can be seen that more people are not ready for the impact that will be caused.